The Identity of Piety in the Digital Age (Study of the Use of Religious Symbols in Social Media) - Abdul Muiz Amir (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2019)
This article is a study of the use of religious symbols on social media that the authors associate with the concept of religious identity. This study targets some dakwah content that has become a trend in social media such as Facebook, WhatsApp and Twitter. The author uses a phenomenological approach as a basis for conducting social analysis, so that the phenomenon of the rise of the use of religious symbols on social media can be manifested well. The result of this study confirm about the indication of the use of religious symbols as an imaging tool from among literalists. Some content also indicates the existence of economic motives in the use of these symbols. I see the phenomenon is part of the symbolic expressions of certain groups in portraying their godly identity through social media